The performance of Chlorella vulgaris growth on mass-scale cultivation - Dini Alvateha; Siska Falentina; Rarasrum Dyah Kasitowati; Sutianto Pratama Suherman; Luthfiana Aprilianita Sari; Sulastri Arsad (Gorontalo State University, 2020)
Phytoplankton have many benefits, including as a primary producer, natural food, bioindicator, and water pollution treatment. For this reason, their availability needs to be managed, one of which is through cultivation. The purpose of this study was to analyze the mass scale cultivation of Chlorella vulgaris. The research was conducted at the Technical Implementation Unit of Freshwater and Brackish Water Aquaculture, Situbondo, using a descriptive method. The data were analyzed statistically using MS. Excel 2016 software, and a multiple linear regression test was carried out to determine the effect of water quality parameters on the growth of C. vulgaris using the SPSS 16.0 application. The cultivation process started from strain preparation, water preparation, tank and culture media preparation, inoculation, fertilization, and then harvesting. The initial density of C. vulgaris used was 145x104 Cell. mL-1 in tank 1 and 188x104 Cell. mL-1 in tank 2. The results showed that the cell density value of C. vulgaris increased every day until it entered the exponential phase, namely on the 4th day of the culture activity, which was 507 x 104 in tank 1 and 536 x 104 Cell. mL-1 in tank 2. Furthermore, the value of water quality parameters that affected the growth of C. vulgaris in tank 1 and tank 2 was dissolved oxygen of 4.82-6.97 mg. L-1, pH 8.2-9.1, transparency of 20-45 cm, temperature was 26.8-28.2 oC, nitrate of 0.10-0.50 mg. L-1, phosphate of 0.75-2 mg. L-1, and salinity of 30-39 ppt.